2014
DOI: 10.4172/2161-1068.1000149
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping Tools for Mycobacterium ulcerans Drawbacks and Future Prospects

Abstract: Mycobacterium ulcerans infection (Buruli ulcer) is a neglected but treatable skin disease endemic in over 30 countries. M. ulcerans is an environmental mycobacteria with an elusive mode of transmission to humans. Ecological and Molecular epidemiological studies to identify reservoirs and transmission vectors are important for source tracking infections especially during outbreaks and elucidating transmission routes. Research efforts have therefore focused on genotyping strains of the mycobacteria from clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…It is important to note that mycolactone production is not limited to M. ulcerans . Indeed, there is a whole family of mycolactone-producing mycobacteria (MPM) including certain strains of M. marinum , M. pseudoshottsii , M. liflandii , and M. xenopi [ 64 , 65 ]. Slight differences in the modular arrangement of genes on pMUM001 mean that they each produce different congeners of mycolactone [ 55 ].…”
Section: Pathogenesis—more Discoveries In Mycolactonementioning
confidence: 99%
“…It is important to note that mycolactone production is not limited to M. ulcerans . Indeed, there is a whole family of mycolactone-producing mycobacteria (MPM) including certain strains of M. marinum , M. pseudoshottsii , M. liflandii , and M. xenopi [ 64 , 65 ]. Slight differences in the modular arrangement of genes on pMUM001 mean that they each produce different congeners of mycolactone [ 55 ].…”
Section: Pathogenesis—more Discoveries In Mycolactonementioning
confidence: 99%
“…During an outbreak in Australia, a PCR study of environmental sources found M. ulcerans in swamp water that was used for irrigation of a golf course (10). In areas of endemicity, reservoirs of the mycobacterium appear to be in biofilms in water sources, aquatic insects, mollusks, and fish (9,11). Mosquito bites have been suggested as a mode of transmission based on epidemiologic research on Australian outbreaks as well as animal studies (12).…”
mentioning
confidence: 99%
“…We were therefore limited to the reliance on PCR and sequencing for our data interpretation. This is not an unusual occurrence in M. ulcerans transmission and epidemiological studies [ 15 , 16 , 34 , 36 ], and newer genotyping methods of sample DNA have positively corroborated this observation.…”
Section: Discussionmentioning
confidence: 62%